(untitled) (CIPEEX, 2022)
IN ORDER TO DEVELOP THE IDEA OF €‹€‹PHOTOVOLTAIC ENERGY AND SEEKING TO DEMONSTRATE ITS HISTORY AND IMPORTANCE, SINCE WE LIVE IN A PERIOD OF GLOBAL REFORMULATION WHEN IT COMES TO ENERGY EFFICIENCY. SINCE PHOTOVOLTAIC ENERGY IS A MEANS OF OBTAINING ENERGY DISCOVERED AROUND 1950, THE AIM IS TO SPREAD THE PREMISE MAINLY IN THE INSTITUTION, HAVING A TEACHING REFERENCE. THERE ARE THREE MAIN CATEGORIES OF SYSTEMS TO BE CHOSEN, EACH ONE WITH ITS ADVANTAGES AND DISADVANTAGES, THESE BEING THE CONNECTED SYSTEM (ON-GRID), THE AUTONOMOUS SYSTEM (OFF-GRID) AND THE HYBRID SYSTEM. EACH SYSTEM HAS ITS ADVANTAGES AND DISADVANTAGES, BUT THE PROCESS IS ESSENTIALLY THE SAME BETWEEN THEM, PRODUCING EXCESS ENERGY DURING THE DAY AND STORING IT FOR USE DURING THE NIGHT OR PERIODS WITH LOW INCIDENCE OF SUNLIGHT. AIMING TO IMPROVE THE TEACHING AND VARIETY OF TOOLS AVAILABLE IN THE TECHNOLOGICAL CENTER OF THE UNIEVANGLICA UNIVERSITY CENTER, WE USE A PHOTOVOLTAIC SOLAR BENCH THAT SIMULATES AN OFF-GRID GENERATION PROCESS, PREVIOUSLY DEVELOPED AND BUILT BY FORMER GRADUATES, TO QUANTIFY THE STUDENTS’ PERFORMANCE THROUGH OF A QUESTIONNAIRE APPLIED BEFORE AND AFTER THE CONTACT WITH THE ELEMETS OF THE BENCH.